Afectaciones e indemnizaciones a la propiedad por contingencias ambientales ocasionadas por la actividad petrolera en la Región Amazónica. Propuesta de un sistema técnico, administrativo y legal operativo - Abad López, César Augusto (2013)
The present research work, whose main interest is related to identifying the experiences that exist regarding the compensation granted to the aboriginal peoples and settlers affected by this oil exploration and exploitation, to subsequently propose an operational technical, administrative and legal system for damages. and property compensation for environmental contingencies caused by oil activity in the Amazon region. The research is structured in six chapters organized as follows: Chapter I, which relates the problem itself to its causes, consequences, objectives, and justification; Chapter II develops the entire theoretical framework, scientifically, technically and legally supporting the variables of this research, as well as the formulation of the hypotheses that will guide this research. Chapter III is aimed at a detailed explanation of the methodology used in this research, as well as the population to be investigated and the techniques used. Chapter IV contains the analysis and interpretation of the results achieved through field work; Chapter V explains the conclusions and recommendations reached, as well as the testing of the hypotheses that guided the research. Finally, as it is a feasible project, the research culminates with the very specific proposal, referring to the design of a technical, administrative and legal operating system for damages and compensation to property due to environmental contingencies caused by oil activity in the Amazon region. . This is a feasible project investigation, which proposes the solution to the problem investigated, which allows us to conclude the design of an operational technical, administrative and legal system. That allows intervention in the processes of damage and compensation to property caused by environmental contingencies. Proposal that allows us to conclude this investigation. DESCRIPTORS: environmental contingencies – oil compensation – regulations.